Construction of an engineered Bacillus subtilis for production of poly-γ-glutamic acids with specific molecular weights - Lin, Yu; Ding, Yiwei; Shu, Lin; Chen, Huizhen; Li, Nan; Duan, Xiaoqun; Zeng, Wei (Frontiers in Microbiology, 2025)
IntroductionPoly-γ-glutamic acid (γ-PGA) with different molecular weight (Mw) exhibits different properties and therefore has a variety of applications. At present, the γ-PGA is mainly produced by Bacillus species. However, the production of γ-PGAs with specific Mws often requires multiple strains, which limits the development and application of γ-PGA.MethodsTo address this limitation, we constructed an engineered Bacillus subtilis strain by deleting hydrolase genes cwlO, pgdS and ggt, and further introduced regulation of PgdS expression under an IPTG-inducible promoter.ResultsWhen the hydrolase genes cwlO, pgdS and ggt in B. subtilis were deleted, the γ-PGA Mw and titer increased by 220.1% (2.42×107 Da) and 47.81% (8.44 g/L), respectively. Furthermore, regulation of PgdS expression enabled dynamic control of γ-PGA Mw. The γ-PGA with Mw ranging from 9.55×104 Da to 2.15×107 Da was produced by change of IPTG addition time in an engineered strain, with the titer of 6.28-8.57 g/L. In the 5-L fermenter, the γ-PGA with Mw ranging from 8.3×104 Da to 1.87×107 Da was produced under optimal conditions.ConclusionIn summary, an engineered strain that can dynamically regulate the γ-PGA Mw and produce γ-PGAs with specific Mws was obtained, and its regulatory range was wider than that of previous studies, which increased the application potential.